The International Robotic Antarctic Infrared Telescope (IRAIT) - Tosti, Gino; Busso, Maurizio; Nucciarelli, Giuliano; Bagaglia, Marco; Roncella, Fabio; Mancini, Alberto; Castellini, Sonia; Mariotti, Mirco; Babucci, Ezio; Chiocci, Gianfranco; Straniero, Oscar; Dolci, Mauro; et al. (SPIE Proceedings, Ground-based and Airborne Telescopes, 2006)
Thanks to exceptional coldness, low sky brightness and low content of water vapour of the above atmosphere Dome C, one of the three highest peaks of the large Antarctic plateau, is likely to be the best site on Earth for thermal infrared observations (2.3-300 μm) as well as for the far infrared range (30 μm-1mm). IRAIT (International Robotic Antarctic Infrared Telescope) will be the first European Infrared telescope operating at Dome C. It will be delivered to Antarctica at the end of 2006, will reach Dome C at the end of 2007 and the first winter-over operation will start in spring 2008, IRAIT will offer a unique opportunity for astronomers to test and verify the astronomical quality of the site and it will be a useful test-instrument for a new generation of Antarctic telescopes and focal plane instrumentations. We give here a general overview of the project and of the logistics and transportation options adopted to facilitate the installation of IRAIT at Dome C. We summarize the results of the electrical, electronics and networking tests and of the sky polarization measurements carried out at Dome C during the 2005-2006 summer-campaign. We also present the 25 cm optical telescope (small-IRAIT project) that will installed at Dome C during the Antarctic summer 2006-2007 and that will start observations during the 2007 Antarctic winter when a member of the IRAIT collaboration will join the Italian-French Dome C winter-over team.